Out of the cave : comparative studies on the themes of unconcealment and transcendence in Plato from a Heideggerian perspective - O'Byrne, Brendan (Trinity College (Dublin, Ireland). Department of Classics, 2002)
In this dissertation I set out to establish a series of closely connected theses which will support the broad thesis of this work that Heidegger’s thinking - especially in the period around Being and Time occupies a proximity with that of Plato. Some commentators have stated that Heidegger is hostile or antithetical to Plato and that his philosophy has a greater affinity with that of Aristotle. Here, I want to put this analysis to the test and argue for a greater affinity between the two thinkers. There are broadly two areas where this productive comparison can be carried out. Heidegger states that any inquiry into beings must include the questioner. The scope of ontological inquiry is the whole and so the inquiry is always into the whole. The inquirer and that which is inquired into together form the whole. To this end I discover that both Plato and Heidegger can be richly compared here. Both thinkers carry out an existential analysis which is integral and organic to their conceptions of ontological inquiry. This theme runs throughout this dissertation and represents one strand of the main thesis - the proximity of Plato’s and Heidegger’s thinking of being.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin